2021
DOI: 10.1371/journal.pntd.0009702
|View full text |Cite
|
Sign up to set email alerts
|

Availability, affordability and stock-outs of commodities for the treatment of snakebite in Kenya

Abstract: Background Annually, about 2.7 million snakebite envenomings occur globally. Alongside antivenom, patients usually require additional care to treat envenoming symptoms and antivenom side effects. Efforts are underway to improve snakebite care, but evidence from the ground to inform this is scarce. This study, therefore, investigated the availability, affordability, and stock-outs of antivenom and commodities for supportive snakebite care in health facilities across Kenya. Methodology/principal findings This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Usually, these life-saving medicines are not readily available in rural high-risk areas where incidences occur frequently. The time delay in receiving antivenom treatment following SBE often results in extensive local tissue damage that can lead to permanent disabilities 45 , 46 . As a result, there is an urgent need to develop better, more efficacious, and affordable treatments for SBE.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, these life-saving medicines are not readily available in rural high-risk areas where incidences occur frequently. The time delay in receiving antivenom treatment following SBE often results in extensive local tissue damage that can lead to permanent disabilities 45 , 46 . As a result, there is an urgent need to develop better, more efficacious, and affordable treatments for SBE.…”
Section: Discussionmentioning
confidence: 99%
“…While this question was intended to reflect stockouts over the past 30 days including today, misinterpretations may have led to data reporting inconsistencies. Literature on commodity availability across several health topics have included measures of stockouts over varying time periods; the WHO SARA reference manual also includes measures of both current availability and past stockouts for the same commodities ( 55 – 58 ). These findings suggest that both measures should be included in future SARA surveys to avoid underestimation of commodity stockouts.…”
Section: Discussionmentioning
confidence: 99%
“…As described, many studies have demonstrated retained efficacy of expired antivenoms, [17][18][19] and it is important to consider whether existing antivenom stocks could be used more efficiently, 16 particularly given the lack of access to these products in low and middle-income settings. [49][50][51] Reports suggest that clinicians are already using expired antivenom products due to lack of availability of in-date products, 25 and the South-East Asia regional office WHO guidelines for managing snakebite endorse this in certain circumstances: 'in patients with severe envenoming, recently expired antivenoms may be used if there is no alternative'. 22 However, we must emphasise that while we and others have demonstrated retained preclinical efficacy of expired antivenoms in mouse models, the clinical efficacy and safety of these antivenoms cannot be confirmed from these assays.…”
Section: Bmj Healthmentioning
confidence: 99%